IMPLIKASI YURIDIS PUTUSAN MK NOMOR 46/PUU- VIII/ 2010 TERHADAP AKTA KELAHIRAN ANAK LUAR KAWIN - Djumikasih Djumikasih (Arena Hukum, 2013)
AbstractThis paper aims to identify and analyze what the juridical implications of the publication of the decision of the Constitutional Court No. 46/PUU-VIII / 2010 on Child Outside Marriage Deed which has been published by the Department of Population and Civil Registration prior to the establishment of the Constitutional Court's decision . The method used in this study is a normative juridical approach legislation. From the discussion, it can be concluded that the Constitutional Court 46/PUU-VIII/2010 Number of Tests on Article 43 paragraph ( 1 ) Marriage Act ( Act No. 1 of 1974 ) when viewed from the angle of legal certainty it will lead to legal certainty . But the decision will not have any juridical implications of the child's birth certificate that has been published outside of marriage and illegitimate child who was born before the date of February 17, 2012, as if enacted would be contrary to the principle of legality is interpreted Article 47 of the Law on the Constitutional Court and Article 28 ( i ) of the 1945 Constitution . Likewise, if the terms of the fairness and usefulness , especially for justice seekers / applicant , the timing of this decision is not fair and not useful , because although the Court granted the petition but the Constitutional Court can not be applied to her . Key words: yuridical implication, birth certificate, children who are born outside of marriage Abstrak Tulisan ini bertujuan untuk mengetahui dan menganalisis apa implikasi yuridis dari terbitnya putusan MK Nomor 46/PUU-VIII/ 2010 terhadap Akta Anak Luar Kawin yang sudah diterbitkan oleh Dinas Kependudukan dan Catatan Sipil sebelum lahirnya putusan MK tersebut. Metode yang digunakan dalam penelitian ini adalah yuridis normative dengan pendekatan perundang-undangan. Dari pembahasan dapat disimpulkan bahwa Putusan MK Nomer 46/PUU-VIII/2010 tentang Pengujian terhadap Pasal 43 ayat (1) UU Perkawinan (UU NO 1 Tahun 1974) jika dilihat dari sudut kepastian hukumnya maka akan menimbulkan kepastian hukum. Akan tetapi putusan tersebut tidak akan mempunyai implikasi yuridis terhadap akta kelahiran anak luar kawin yang sudah terbit dan anak luar kawin yang sudah lahir sebelum tanggal 17 Februari 2012, karena jika diberlakukan akan bertentangan dengan asas legalitas yang ditafsirkan dari Pasal 47 UU Mahkamah Konstitusi dan Pasal 28 (i) UUD 1945. Demikian juga jika ditinjau dari sudut keadilan dan kemanfaatan, khususnya bagi pencari keadilan /pemohon, waktu pemberlakuan putusan ini menjadi tidak adil dan tidak bermanfaat, karena meskipun MK mengabulkan permohonannya tetapi Putusan MK tersebut tidak dapat diberlakukan kepadanya.Kata kunci: implikasi yuridis, akta kelahiran, anak luar kawin.